ANALYSIS OF RIVERS ON THE MAP, IN PRIMARY EDUCATION - Nicoleta-Ioana BOGDAN (Romanian Review of Geographical Education)
The purpose of this study is to identify the effects of individual use of a worksheet in analyzing the network of flowing waters in a territory represented on a map and partially known by the students. 16 fourth grade students participated in the study. In the activity, three stages were completed: in the first stage, the students solved a pre-test with 10 True-False items about the flowing waters of the studied territory; in the second stage they solved the tasks in a worksheet based on the analysis of flowing waters represented on the map; in the third stage the students solved a post-test similar to the one in the first stage. The results show that the students, after analyzing the map with the help of the worksheet, in the formative intervention, have a greater volume of knowledge about the running waters of the commune where they live, which proves the effectiveness of this worksheet